CURCUMA CINNABARINA AND C. EBURNEA (ZINGIBERACEAE: ZINGIBEROIDEAE), TWO NEW SPECIES FROM THAILAND - Leong-Škorničková, J.; Soonthornkalump, S.; Suksathan, P. (Edinburgh Journal of Botany, 2020)
Curcuma cinnabarina and C. eburnea (Curcuma subg. Ecomatae, Zingiberaceae), two new species from Thailand, are described and illustrated here. They are compared with the morphologically closest species Curcuma rubrobracteata and C. pierreana, respectively. Detailed descriptions, colour plates, and information on their distribution, ecology, phenology and uses are also provided. Preliminary IUCN conservation assessments of these species are proposed.